Yartsagunbu: transforming people's livelihoods in the Western Himalaya. Issue 2 (18th December 2018) - Yadav, Pramod Kumar; Saha, Subhajit; Mishra, Ashish Kumar; Kapoor, Mohnish; Kaneria, Manendra; Kaneria, Manish; Dasgupta, Sabyasachi; Shrestha, Uttam Babu
Abstract: Rural communities in developing countries extract provisioning ecosystem services from the natural environment to meet their subsistence needs, generate cash income and create employment opportunities. Caterpillar fungus Ophiocordyceps sinensis, known as yartsagunbu in Tibet and in the literature on this subject, is a medicinal resource extracted by the mountain communities of the Himalaya. Studies of the contribution of the fungus to local livelihoods in the Indian Himalaya are scarce. We investigated trade and harvest and analysed the contribution of caterpillar fungus to household economies in 32 villages in Dhauliganga Valley, Nanda Devi Biosphere Reserve, in the Western Himalaya. Caterpillar fungus harvesting has become an integral part of local livelihoods in the study area, and on average contributes c. 74% of household cash income. The majority of harvesters perceived that harvesting had become more difficult during 2010–2015 as a result of competition and a decline in abundance of the species. The mean annual per capita harvest declined by 54 pieces during 2011–2015. Increasing harvesting and trade, coupled with the dependency of local communities on the fungus, may result in greater extraction of the resource for short-term economic benefits, and could eventually lead to depletion and ecological damage. Harvesting of the fungus has already created environmental, legal and social challenges, although it has become a lucrative livelihood opportunity. The ongoing decline of the fungus threatens local livelihoods. Good governance and livelihood security should be integrated with biodiversity conservation when devising government policies and plans for sustainable management of the caterpillar fungus.